Management Skills and Organizational Issues Toward Change Management Model: The Case of Rural Community Colleges in the Philippines - Pocaan, Jordan Miranda; Lomibao, Hennie Pama; Campos, Grace Revilla; Hermosa, Kristel Ann Rosacena; Arimado, Faustino Jr.; Ballatan, Abegail Enriola; Dumo, Karen Pesonila; Dumo, Jayson; Espineda, Menchie; Alej, Joan Conepcion (Jurnal Pendidikan Progresif, 2023)
Management Skills and Organizational Issues Toward Change Management Model: The Case of Rural Community Colleges in the Philippines. Objectives: The purpose of the research was to investigate the management abilities of administrators, teachers, and non-teaching personnel, as well as organizational concerns to propose recommendations to solve this issues. Methods: This study used sequential explanatory mixed methods research with two phases of data gathering and analysis. It collects and analyzes quantitative data through survey questions before gathering qualitative data through focus group discussions (FDG). Findings: Following the four organizational cultures - clan, market, adhocracy, and hierarchy - the diverse management abilities of administrators, teachers, and non-teaching staff are described by the study's findings. In addition, the fundamental difficulties of rural community colleges in terms of organizational performance and adaptation, organizational weakness, and internal conflict are discussed. The research also produces the REACT model for change management based on its results. Conclusion: Community colleges in rural areas must adopt change management that addresses their organizational challenges and is based on their management skills. Furthermore, additional funding, assistance programs, and manual development for academics and staff are proposed. Keywords: community colleges, change management, organizational culture, philippine higher education.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202336